Ucapan Bahagia dan Hubungannya dengan Khotbah di Bukit Secara Keseluruhan - Naomi Sapan (CARAKA: Jurnal Teologi Biblika dan Praktika, 2020)
Abstract. The Beatitude is often misunderstood as a beautiful words yet  irrelevant and impossible to practice in daily life. However, in the context of the  rest of the Sermon on the Mount and Discourses of the entire book of Matthew, the Beatitude is important because the beatitude is the fundamentally values of the citizens of the Kingdom of God. The happiness as the citizen of God’s Kingdom is very began in their inner life because they are be connected to God, so the happiness is only possible if the people have a fellowship with God who extending and flowing His happiness to them. When the people of the Kingdom of God be connected to the world and living in the daily life their function as salt and light to be realized in practical ethics that relating to all aspects of the social and religious community where they are. The condition of 'happiness' is not related to ownership of something material but happiness or be blessed is identical to their identity as citizens of the Kingdom of God. Happiness that begins when someone responds to the calling of repentance and begins life as a citizen of the Kingdom in fellowship with God. Happiness is also not determined by the promise that following. The following promise is a result of their attitude heart as the blessed one. Regarding to the promise, it must be understood as an eschatological expectations; in eschatology "already but no yet", it has begun but its fulfillment is towards to the future and keep them living to be blessed one.Abstrak. Ucapan bahagia itu sering disalahpahami sebagai kata-kata indah namun tidak relevan dan mustahil untuk dipraktikkan dalam kehidupan sehari-hari. Namun, dalam konteks sisa Khotbah di Bukit dan Khotbah dari seluruh kitab Matius, Ucapan Bahagia penting karena ucapan bahagia adalah nilai-nilai fundamental dari warga negara Kerajaan Allah. Kebahagiaan sebagai warga Kerajaan Allah sangat dimulai dalam kehidupan batin mereka karena mereka terhubung dengan Tuhan, sehingga kebahagiaan hanya mungkin terjadi jika orang-orang memiliki persekutuan dengan Tuhan yang memperluas dan mengalirkan kebahagiaan-Nya kepada mereka. Ketika orang-orang Kerajaan Allah terhubung ke dunia dan hidup dalam kehidupan sehari-hari, fungsi mereka sebagai garam dan cahaya untuk diwujudkan dalam etika praktis yang berkaitan dengan semua aspek komunitas sosial dan keagamaan di mana mereka berada. Kondisi 'kebahagiaan' tidak terkait dengan kepemilikan sesuatu yang material tetapi kebahagiaan atau diberkati identik dengan identitas mereka sebagai warga Kerajaan Allah. Kebahagiaan yang dimulai ketika seseorang menanggapi panggilan pertobatan dan memulai hidup sebagai warga negara Kerajaan dalam persekutuan dengan Allah. Kebahagiaan juga tidak ditentukan oleh janji yang mengikutinya. Janji berikut ini adalah hasil dari sikap hati mereka sebagai yang diberkati. Mengenai janji itu, harus dipahami sebagai harapan eskatologis; dalam eskatologi "sudah tetapi belum", itu telah dimulai tetapi pemenuhannya menuju masa depan dan membuat mereka hidup untuk diberkati.